A process-oriented analysis of parent acculturation, parent socio-cultural stress, family processes, and Latina/o youth smoking and depressive symptoms. (May 2016) - Lorenzo-Blanco, Elma I.; Schwartz, Seth J.; Unger, Jennifer B.; Romero, Andrea J.; Cano, Miguel Ángel; Baezconde-Garbanati, Lourdes; Córdova, David; Oshri, Assaf; Santisteban, Daniel A.; Des Rosiers, Sabrina E.; Huang, Shi; Villamar, Juan A.; et al.
Abstract: Latina/o youth in the U.S. are often characterized by elevated rates of cigarette smoking and depressive symptoms, and these rates appear to vary by youth acculturation and socio-cultural stress. Scholars suggest that parents' cultural experiences may be important determinants of youth smoking and depressive symptoms. However, few studies have examined the influence of parent acculturation and related stressors on Latina/o youth smoking and depressive symptoms. To address this gap in the literature, in the current study we investigated how parent-reported acculturation, perceived discrimination, and negative context of reception affect youth smoking and depressive symptoms through parent reports of familism values and parenting. The longitudinal (4 waves) sample consisted of 302 Latina/o parent-adolescent dyads from Los Angeles ( N  = 150) and Miami ( N  = 152). Forty-seven percent of the adolescent sample was female ( M age = 14.5 years), and 70% of the parents were mothers ( M age = 41.10 years). Parents completed measures of acculturation, perceived discrimination, negative context of reception, familism values, and parenting. Youth completed measures regarding their smoking and symptoms of depression. Structural equation modeling suggested that parents' collectivistic values (Time 1) and perceived discrimination (Time 1) predicted higher parental familism (Time 2), which in turn, predicted higher levels of positive/involved parenting (Time 3). Positive/involved parenting (Time 3), in turn, inversely predicted youth smoking (Time 4). These findings indicate that parents' cultural experiences play important roles in their parenting, which in turn appears to influence Latino/a youth smoking. This study highlights the need for preventive interventions to attend to parents' cultural experiences in the family (collectivistic values, familism values, and parenting) and the community (perceived discrimination).